Developing Drought Tolerance in Field Crops towards Current Century: An Integrated Bio-molecular Approach - Shil, Sanjoy; Shashank, Ankam; Rambabu, Bhukya; Ponaganti, Shiva Kishore; Dewanjee, Sujaya (International Journal of Bio-resource and Stress Management, 2024)
Drought stresses are foremost threat to plant growth, productivity as well as sustainability towards agriculture through worldwide. Some of the classical breeding approaches have been attempted to develop crop performance towards stress without significant success and so therefore, recently genetic engineering in crop plants is recognized as an alternative strategy to generate drought tolerant crop plants. Various integrated biological approaches have been undertaken to overcome such drought hurdles in achieving the full potentiality of the plant growth and production as well as improving the drought tolerance in different field crops. Some approaches are commonly used to identify genes related to drought tolerance and genes to be identified which are involved in processes known to be critical for drought tolerance; whose expression is regulated by drought stress and that consists in the identification of drought tolerance determinants based on functionality. Plant researchers have developed several spurts of biological novel ‘Omics’ technologies viz. genomics, transcriptomics, proteomics and metabolomics etc to engineer plant stress tolerance. In this review, an attempt has been made to summarize the current information based on recent literature towards recent understanding as well as latest advancement related to the adverse effect of plant under drought and their adaptations or tolerance towards such abiotic stress with a focus on the identification of drought tolerance mechanisms by soil management practices, crop establishment and exogenous application of growth regulators by regulating an appropriate level of water due to osmotic adjustment and stomatal performance etc at an integrated biological level of approach.